Shaking Dust and Stopping Clouds: the Aesthetics of Performance in Two Sets of Poems by Zang Maoxun and Wu Mengyang. (3rd July 2019) - Zhang, Rachel Junlei
Abstract : Literary studies on the aesthetics of performance in the late Ming have paid scant attention to critics' poetic writings as a form to express their thoughts and feelings toward performance. This paper examines poems by Zang Maoxun (1550–1620), collected in Fubao tang ji, as well as poems by his social coterie in Jinling and Wuxing, that focus on the social and poetic aspects of performance. In recent scholarly discourse, Zang Maoxun's role as editor and publisher of Yuan performative texts has been well covered, but neither his status as a poet nor the poetic exchanges within his social network have been properly investigated as sources for information on Chinese theater. This paper focuses on non-dramatic forms of literature, poetry in particular, in order to unveil the social occasions that precipitated his poetic compositions and the treatment of musical performance in his poetry.